Implementasi Manajemen Sumber Daya Manusia Digital Pada UMKM Studi Kasus di Kemari Coffee - Aloysius Dhimas Trikurnian (EXERO : Journal of Research in Business and Economics, 2023)
The Covid-19 pandemic cannot be told as it’s over, life is still going on. People need to adapt with new life habit especially Usaha Mikro Kecil dan Menengah (UMKM) where it needs to be experiential seriously by all of the people in supporting national economy in Indonesia. One of the most important adaptation processes done by UMKM is the human resource management by digitalization program to make more efficient and relevant in the future. Digitalization study implementation in UMKM will be the most important thing to do soon. In that case, this research analyzed digital human resource management implementation in UMKM with case study in Kemari Coffee. Descriptive qualitative method is used in this research to clarify the concept of digital human resource management that has applied in UMKM Kemari Coffee. The journal concluded that Kemari Coffee has not applied digital human resource management overall. Part of digital human resource management that already has applied namely E-Recruiment Selection, E-Selection Induction, and E-Reward Compensation Management, meanwhile those haven’t applied namely E-Performance Appraisal, E-Training Development, and E-Learning Talent Management.